Application Regulation Finance to Business Process Management Through and Adaption Technology on Smes in Makassar City - Andi Harmoko Arifin; Ira Geraldina; Ni Luh Kardini; Muhammad Rizkillah (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to examine variables related to the implementation of FinTech on SMEs in Makassar City using a quantitative research approach. Variables studied are related to Financial Regulations, Adoption Technology, and Business Process Management. The sampling technique in this research was stratified sampling, dividing groups or categories, and then these categories were selected using simple random or systematic samples. All variables used use instruments with several indicators and parameters that help the quantitative data analysis process. Quantitative analysis calculations using statistical methods using the software Structural Equation Model (SEM) PLS. The research results showed that a direct relationship between technology and business process management had a positive and significant effect. In contrast, FinTech had a positive and significant effect on business process management, regulation finance, and the adoption of technology. There was a direct influence between regulation finance's positive and significant effect on FinTech as well as indirect influences. Regulation Finance has a positive and significant effect on Business Process Management through Adaptation Technology. However, Regulation Finance does not have a significant effect on Business Process Management through FinTech.